2012
DOI: 10.2478/v10096-012-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of bio- and magnetostratigraphy of Badenian sequences from western and northern Hungary

Abstract: Lithological, magnetostratigraphic and paleontological (nannoplankton, foraminifers, molluscs) studies were carried out on the Badenian successions of boreholes Sopron-89, Nagylózs-1 and Sáta-75 in Hungary. The correlations with the ATNTS2004 scale show that the Badenian sedimentation began during Chron C5Br thus the earliest Badenian deposits are missing in the sections. The first occurrence of Orbulina suturalis Brönnimann has been observed in Subchron C5Bn.1r, at 14.9 Ma. Although it is older than the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
2
22
0
1
Order By: Relevance
“…This could in di cate heterechroneity of this trans gres sion in a SW to NE di rec tion (?through tectonical in flu ences). Selmeczi et al (2012) supported this hy poth e sis when magnetostratigraphical re sults showed dif fer ent ages for the Mid dle Mio cene transgresion between west ern and east ern Hun gary.…”
Section: Correlation With Other Central Paratethys Basinssupporting
confidence: 56%
See 1 more Smart Citation
“…This could in di cate heterechroneity of this trans gres sion in a SW to NE di rec tion (?through tectonical in flu ences). Selmeczi et al (2012) supported this hy poth e sis when magnetostratigraphical re sults showed dif fer ent ages for the Mid dle Mio cene transgresion between west ern and east ern Hun gary.…”
Section: Correlation With Other Central Paratethys Basinssupporting
confidence: 56%
“…In the Carpathian Foredeep it is con centrated in its south ern and cen tral part (Švábenická, 2002). Helicosphaera waltrans is lack ing in Po land (Oszczypko and Oszczypko-Clowes, 2012), east ern Hun gary (Selmeczi et al, 2012) and the north ern part of the Pannonian Ba sin in Slovakia and these transgressive de pos its should be youn ger than 14.37 Ma (LCO of H. waltrans). This could in di cate heterechroneity of this trans gres sion in a SW to NE di rec tion (?through tectonical in flu ences).…”
Section: Correlation With Other Central Paratethys Basinsmentioning
confidence: 99%
“…In other bas ins, world-ocean bioevent ages for cal i bra tion of detected magnetostratigraphical chrons were used. In the Pannonian Ba sin, it ap peared in the re verse chron cor re lated with C5Bn.1r Chron (15.03-14.87 Ma; Selmeczi et al, 2012). A sim i lar age is sug gested for the Al pine Foredeep Ba sin (AEoriae et al, 2004), while the spe cies' first oc cur rence in the Styrian Basin is dated to the nor mal Zone C5Bn.1n (14.87-14.78 Ma).…”
Section: Interregional Correlations and Bioevents Timingmentioning
confidence: 95%
“…Orbulinas are the most widely dis trib uted in dex microfossils in this time in ter val, which oc cur in all Cen tral Paratethys bas ins (e.g., AEoriae et al, 2004AEoriae et al, , 2009Tomanová-Petrová and Švábenická, 2007;Spezzaferri et al, 2009;Selmeczi et al, 2012;de Leeuw et al, 2013;Peryt, 2013;Doláková et al, 2014;Holcová et al, 2015a, b;Gozhyk et al, 2015;Rybár et al, 2015). The FO of Orbulina rep re sents the base of the lo cal biozone of Praeorbulina-Orbulina suturalis (Cicha et al, 1975).…”
Section: Interregional Correlations and Bioevents Timingmentioning
confidence: 99%
See 1 more Smart Citation